ANALISIS EFEKTIVITAS TALENT DEVELOPMENT MELALUI COMPETENCY MAPPING DAN PENGARUHNYA TERHADAP CORPORATE PERFORMANCE - Trika Gunawan Adiwibowo; Paulina Harun (Indonesia Banking School, 2015)
The concept of business integration putting Human Resource (HR) as major capital to support company’s competitive advantage ability. Therefore in the current practice, effectiveness of the talent development role is a major concern for HR practitioners. On the other hand, competency mapping plays a significant and positive effect on the implementation of talent development strategy. The effectiveness of talent development can be achieved if the company/ organization can implement competency mapping program in order to determine the composition and measurement estimation of the company's HR quality. Implications of the talent development has significant and comprehensively affect the escalation of employee’s competency and employee’s productivity respectively. In addition, the escalation of employee’s competency and employee’s productivity will eventually positive effect on corporate performance.In general, this research focusing on mining contractor company in Indonesia shows that the result in line with the explanation above. There is a significant and positive relation among competency mapping, talent development, employee competeny, employee productivity and corporate performance. The role of competency mapping and talent development is not just for employee development, but in wider point of view this is a strategic goal to achieved business integration based on HR approach. The main implications from this research is shows that talent development is the solution for the company’s expectation related with the HR/ manpower qualities.Finally, the effectiveness of the role of competency mapping and talent development can be achieved if the Company (through corporate management) is committed to support its implementation. Business integration requires participation from all organization member, including HR pratitioners, employees and corporate management in order to achieve a sustainable advantage and synergy.Keywords : human resources (HR), competency mapping, talent development, employee competency, employee productivity, corporate performance